Prática pedagógica e espaço escolar: desafios e concepções - Nascimento, Elizângela Gomes (2020)
This reaserch aims to understand the usage of the educational space from an EMEF (Municipal School of Children Education) inside a Centro Educacional Unificado – CEU (Unified Educational Center), and what it representes to teachers and their fundamental students, interdisciplinary cycle and autoral (early years and finals). OUr investigation was based on the following propositions: how teachers and students use the school space to teaching and learning? How we could propose the usage of this space in order to raise the quality of education based on the students’ authors’ narratives? How school’s introduction can colaborate with the pedagogical practice? A semistructured interview was used to drive investigation and data acquiring among teachers who have benn working in that specific school since its foundation and students from different years from fundamental grade, from the 6th to 9th grades. We tried to exam the teacher’s narratives inside their professional environments under the view of the usage of the CEU’s education space. Towards the proposed, our mission was search for comprehension in how teachers use the school space during the learning process according to the CEU educational perspective after fifteen years of working. Towards, it is possible to infer that we cannot underestimate the usage of its innovative project for the school’s architecture and education. We verified that the continous education is damaged in its structure and the school administration is benefited from the changes, increasing the project abandonment in its dialogical concepts, in educational quality, full time education, Education drive city and democratization. The research is based on the following outhors: Gadotti (2004, 2008, 2013), Tardif (2002), Viñao Frago e Escolano Benito (2001) e Libâneo (1994, 2004).